Pengenalan dan Pemanfaatan Daun Gedi Merah Sebagai Tanaman Obat Keluarga di Lingkungan RT 01 RW 06 Kelurahan Lolu Selatan - Viani Anggi; Priskila El Sara (Jurnal Medika: Medika, 2025)
Red Gedi leaves (Abelmoschus manihot L.) are one of the traditional plants with great potential as family medicinal plants (TOGA), yet their utilization remains limited within the community. This study aims to introduce and enhance the use of Red Gedi leaves as family medicinal plants in RT 01 RW 06, Lolu Selatan Subdistrict. The method employed was a qualitative descriptive approach through counseling, demonstrations, and direct community assistance. Activities included socialization of the benefits of Red Gedi leaves, cultivation techniques, processing methods, and their application as traditional medicine. The results indicated an increase in community knowledge regarding the health benefits of Red Gedi leaves, which contain antioxidant and anti-inflammatory properties and may help alleviate various health problems such as hypertension, diabetes, and digestive disorders. The community also showed enthusiasm in cultivating Red Gedi leaves in their home gardens. This program successfully increased community awareness of the importance of utilizing family medicinal plants as preventive and curative efforts that are simple, affordable, and safe, with an improvement rate of 60–70%. It is recommended to provide continuous assistance and expand similar programs in other areas to maximize the benefits of traditional medicinal plants in supporting public health.